Chromone hybrids as interleukin-6 and acetylcholinesterase inhibitor for treatment of Alzheimer's disease: Design, docking, synthesis and evaluation - Shivam Mishra; Sukhvir Kaur; Gulshan Bansal; Yogita Bansal (Elsevier, 2024)
The course of Alzheimer's disease (AD) is largely influenced by interleukin-6 (IL-6) and acetylcholinesterase (AChE). Therefore, concurrent suppression of these two targets is a rational approach for the development of anti-AD molecules. The study is aimed to design a molecule with pharmacophore capable of inhibiting both the targets. Four series are designed by coupling a chromone moiety (a pharmacophore that inhibits IL-6) with a N,N-disubstituted amine (that inhibits AChE) through a linker (1-4 carbon chain). The in silico studies on the designed compounds led to the identification of 16 best-fit compounds having good oral bioavailability and blood brain barrier permeability. All 16 compounds were synthesized and evaluated for anti-AChE activity. Six compounds showing >45 % inhibition of AChE at 1 μM concentration are further evaluated for BuChE (butyrylcholinesterase) and IL-6 inhibitory activities. Compound YS3g is the most potent inhibitor of EeAChE (IC50 = 0.45 μM) and of IL-6 (IC50 = 0.46 μM). Subsequently, it is found to show dose-dependent effects in STZ (streptozotocin)-induced memory deficit model at three doses (0.2, 0.4 and 0.8 mg/kg). At higher dose (0.8 mg/kg), it reverses the deficit as also supported by histopathological studies. The findings reveal that a chromone nucleus coupled with a piperazine via a three-carbon linker may be a useful template for developing novel moieties against AD.